Coaxial helium electrospray for single-particle imaging at X-ray free electron lasers - Safi Rafie-Zinedine; Joachim Schulz; Johan Bielecki; Michael Heymann (Journal of Synchrotron Radiation)
Single-particle imaging at X-ray free-electron lasers relies on suitable sample injection of nanoscale macromolecules and particles into the gas phase at room temperature. A coaxial liquid-sheet strategy considerably extended the range of suitable samples to include conductivities from zero to 40000 µS cm−1 – a more than about an eightfold increase in range compared with conventional electrosprays. A helium chamber atmosphere in combination with an engineered gas-sheet protected aerosol formation against corona discharge and reduced background noise more than threefold. These results suggest new avenues to qualify ever more demanding biological and material science samples for single-particle imaging in the future.